The effect of short-term heat stress on protein synthesis signaling in isolated rat skeletal muscle - Ayumi Goto; Keiichi Sekine; Rieko Oshima; Ichika Sakon; Mayu Iwamoto; Tomohiko Osaki; Kotaro Haga; Tatsuya Hayashi; Tatsuro Egawa (Japanese Society of Physical Fitness and Sports Medicine, 2018)
Heat stress (HS) is a potent stimulus for activating glucose metabolism in skeletal muscles. However, the effect of short-term HS on protein turnover in skeletal muscles is unclear. This study aimed to investigate the effect of short-term HS on protein synthesis and protein degradation in skeletal muscles. The epitrochlearis muscle was isolated from male Sprague-Dawley rats weighing 150-160 grams (g) and incubated with or without HS at 42°C for 10 or 30 min in alpha minimum essential medium. HS for 30 min significantly decreased phosphorylation of 70-kDa ribosomal protein S6 kinase at Thr389 and 4E-binding protein 1 at Thr37/46. Correspondingly, HS for 30 min decreased the rate of protein synthesis. In contrast, HS had no effect on the expression of autophagy-related proteins, including microtubule-associated protein light chain 3 and p62, or on the mRNA expression of muscle-specific ubiquitin ligases, including muscle RING-finger 1 (MuRF1) and atrogin-1/MAFbx. These findings suggested that short-term HS for approximately 30 min is a physiologically relevant stimulus that suppresses protein synthesis signaling in skeletal muscles.